The Effect of Green Marketing, Brand Image, and Price Perception on Purchase Decisions for Aqua Brand Packaging Drinking Water - Oktian Frendy Kurniawan; Siti Ning Farida (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of green marketing, brand image, and price perception on purchasing decisions for AQUA brand bottled drinking water. Green marketing is an important factor in attracting consumers who are increasingly concerned about the environment, while brand image plays a role in forming positive perceptions of product quality. In addition, price perception also influences purchasing decisions, especially in a competitive market. The research method used is quantitative with a survey approach. Data were collected by distributing questionnaires to respondents who are AQUA consumers. The analysis was carried out using multiple linear regression to determine the simultaneous and partial effects of independent variables on purchasing decisions. The results showed that green marketing, brand image, and price perception simultaneously had a significant effect on purchasing decisions. Partially, green marketing did not have a significant effect on purchasing decisions. Brand image had a significant effect on purchasing decisions, where consumers were more likely to buy products with a strong and trusted brand image. Meanwhile, price perception influenced purchasing decisions with consumers tending to choose products with prices that were considered comparable to the benefits obtained.